Elements of the management of norms and their effects on the sense of virtual community. Issue 3 (29th April 2014) - Petrič, Gregor; Petrovčič, Andraž
Abstract : Purpose: – The purpose of this paper is to investigate how decisions of managers and administrators of online communities on norms and rules affect the sense of virtual community (SOVC), which is an important factor of the quality of online information. Design/methodology/approach: – The study followed a two-level research design based on 970 online community members, nested within 36 online communities. Data collection consisted of two stages: first a web survey of a sample of online community members was conducted, followed by a web survey of administrators of the same online communities. A two-level hierarchical regression analysis was used to test the hypotheses. Findings: – The empirical results suggest that prominence of rules under the condition of members' participation in their creation, presence of reputation mechanisms, and content moderation contribute significantly to the SOVC, while presence of lighter sanctions and interactive moderation do not. Research limitations/implications: – Since this study is based on web forums, the validity of the proposed hypotheses for other types of online communities cannot be firmly established. Additional elements of online community management could be considered for a stronger system-level explanation of the SOVC. Practical implications: – The study demonstrates that online community administrators need to be considerate in creating and enforcing norms, as their decisions have an impact on the SOVC and consequently on the quality of online information. Originality/value: – The literature considers many factors of the SOVC but none of the previous studies have considered how community management is associated with this phenomenon.